Komunikasi Digital Dalam Produksi Konten “Kamus Politik” Tiktok @cnnindonesia - Anhar, Nazhea Rachel Ainayya; Dirgantara, Pradipta (eProceedings of Management, 2024)
The creation of this project is underpinned by the rapid advancements in technology witnessed in recent years, notablyin computers, the internet, and mobile devices, reshaping our lifestyles, professions, and social interactions, andembedding digital communication as an indispensable component across various spheres of life. The primaryobjective of this endeavor is to delve into the realm of digital communication within the context of producing contentfor CNN Indonesia's "Political Dictionary." The theoretical framework employed encompasses digital communicationtheory, political communication, and social media studies. Methodologically, the research relies on observationaltechniques to track political discourse trends across diverse social media platforms and online searches to gauge thepolitical climate in Indonesia comprehensively. The research findings reveal that the development of the "PoliticalDictionary" video series, centering on the 2024 election, epitomizes the application of digital communication theoryby disseminating pertinent election-related information, including presidential debates and party listings.Consequently, it can be inferred that the "Political Dictionary" series fosters effective political discourse, evident inthe multitude of interactions on TikTok, reflecting audience enthusiasm. Through 15 videos, both serial and nonserial, this content successfully reaches a young audience, particularly Generation Z. Keywords-digital communication, political communication, social media, TikTok, creative content